Structures and energetics of low-index stoichiometric BiPO4 surfaces. Issue 32 (16th July 2019) - Xu, Yuan; Ma, Xinguo; Hu, Jisong; Xu, Ang; Wang, Zhuoran; Huang, Chuyun
Abstract : Four low-index surfaces of monazite BiPO4 in the Wulff shape are investigated. Abstract : The surface properties of BiPO4 exert a significant effect on the photocatalytic performance under ultraviolet irradiation, but they have not been well explored, either experimentally or theoretically. Herein, for the first time, we systematically studied the structures and energetics of four low-index stoichiometric surfaces of monazite BiPO4 using density functional theory. A new scheme is proposed to correct the surface energy and compare this with the average surface energy. Both of the two schemes for the surface energies indicate that the order of the surface energies is (100) < (010) < (011) < (001), which is not completely consistent with their surface dangling bond densities. The main reason is incomplete PO4 tetrahedrons, namely, the existence of dangling P–O bonds in the bare (001) plane. However, only dangling Bi–O bonds are found in the other three low-index surfaces. It is obvious that the dangling bond density of the Bi atoms and the intact PO4 tetrahedrons are two crucial factors in the surface stability. Correspondingly, the differences in the planar-averaged electron density and the work function are presented to describe the charge distribution close to the surface. Furthermore, the equilibrium morphology calculated using the Wulff construction suggests that the (001), (010), (011) and (100) facets account for 15%, 33%, 16% and 36%, respectively. The two low-energy (100) and (010) facets dominate in the Wulff shape and make up almost 69% of the total crystal shape area. This work will provide theoretical guidance for the further design of effective BiPO4 -based photocatalysts.